Categorization of human monkey-pox from skin lesion images based on transformer and ensemble learning using GRADCAM - Hassan, Ibne; Tahsin, Raida Mobashshira; Toma, Sadia Shara; Utchhash, Tausif Tazwar Quadria (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.